Starting small and building out with Ernie Stringer: Personal insights into action research and educational change. Issue 4 (December 2014) - Dustman, Eric L; Kohan, Mark B; Stringer, Ernie T
The impact of Ernie Stringer's life and work over the last five decades is far-reaching and shows a sustained commitment to community development and educational change. This interview, the third in a series about action research and its most influential thinkers, provides insight into Ernie's diverse and devoted career with action research. Because Ernie is a leading scholar and practitioner in the field, his wisdom and experience strengthen the ability of other action researchers and citizens to create "big differences from small actions."